Biometric Course Attendance Monitor - Benjamin Kommey (Institute of Research and Community Outreach - Petra Christian University, 2018)
Abstract. During lectures, unless a lecturer clearly spots out that a particular student is absent, it becomes difficult to do so in an institution where manual system or sheet of papers are used for recording attendance. Students can sign the signatures of their colleagues and hence fill in the particulars of their absentee friend during attendance recording. This attitude employed by students nullifies the very purpose of taking attendance during lectures. Fingerprints are unique to each individual. They are considered as the best and fastest method for biometric identification. The hand or fingers of a student cannot be passed on to a colleague and hence his/her fingerprints. In an academic environment, the ability of a student to make a copy of his/her fingerprint for the purpose of proxy attendance recording is minimal or non-existent. A student has to be present at a lecture before he/she can be verified biometrically. In this paper, we present a fingerprint-based Biometric Course Attendance Monitor for recording attendance in educational institutions. The system comprises of an embedded device and a web application. The embedded device records attendance electronically after a student is identified using fingerprint recognition system. Attendance is recorded and stored locally on the embedded device. The device is then interfaced with a web application for managing the attendance records of students. Keywords: Biometric, Fingerprint, Attendance, Student, Lecture.